Turning outsourcing inside-out? The case of the mindfulness in schools project. Issue 2 (3rd March 2020) - Kirk, David
ABSTRACT: This paper provides an account of programmes in schools developed by the Mindfulness in Schools Project (MISP) as an example of the outsourcing of Health and Physical Education. The purpose of the paper is to show that outsourcing, is complex and does not match some of the expectations associated with this neoliberal practice. Responding to the argument that outsourcing is a form of curriculum development from the 'outside-in', I suggest that the MISP's work with schools is in contrast a form of 'turning outsourcing inside out'. I show that the success of the MISP programmes rested on teacher advocacy and commitment from inside schools. I argue that the practices of the MISP placed limits on the extent to which it might generate revenue to protect the integrity of its approach. I conclude by considering whether these practices to safeguard integrity were justified, or whether they were another example of what have been called 'intrusive pedagogies'.